Thigh muscle-tendon injuries in athletes: From the analysis of injury mechanisms to a novel diagnostic technique and surgical treatment - Jokela, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2025)
Thigh muscle-tendon injuries are common among athletes. These injuries can be severe and require long rehabilitation or even surgical treatment. They also tend to recur quite often, causing prolonged time off from sports. More research on the etiology, diagnostics, and treatment of these injuries is needed to develop better prevention and management. This study was performed to investigate the mechanisms of thigh muscle-tendon injuries, a novel scanning position for diagnosing proximal hamstring tendinopathy, and patient outcomes after surgical treatment of hamstring injuries. In the study of mechanisms of high-grade hamstring injuries in professional football (soccer in this thesis), we found injuries occurring during high-speed movements, typically involving hip flexion, knee extension, and trunk flexion, and most commonly affecting the biceps femoris. In addition to sprinting and stretching, also mixed-type injuries occurred. Most (80%) of the rectus femoris injuries among male professional soccer players occurred during kicking, often causing total rupture of at least one tendon. Sprinting injuries also led to total ruptures, whereas change of direction only caused partial tears. In the study of severe adductor longus injuries in professional soccer players, we found closed kinetic chain actions, such as reaching for the ball, being most frequently present at the time of injury. Hip extension, abduction, and external rotation were typically seen. In proximal hamstring tendinopathy, diagnostics can be very challenging, and the condition may be difficult to treat. In this study, we presented the novel hip flexion scanning position and proved its additional value in magnetic resonance imaging diagnostics of proximal hamstring tendinopathy. In a systematic review, we found that surgical treatment of hamstring tendon ruptures leads to successful outcomes, especially when surgery is performed early.

Reiden lihas-jännevammat urheilijoilla: Vammamekanismien analyysistä uuteen diagnostiseen menetelmään ja leikkaushoitoon Reiden alueen lihas-jännevammat ovat varsin yleisiä urheilijoilla. Vammat uusiutuvat herkästi ja voivat olla vakavia, vaatien pitkää kuntoutusta tai jopa kirurgista hoitoa. Näistä syistä tarvitaan lisää tutkimusta vammojen etiologiasta, diagnostiikasta ja hoidosta, jotta ennaltaehkäisyä ja hoitoa voidaan kehittää. Tutkimusaiheinamme olivat reiden lihas-jännevammojen mekanismit, uusi kuvausasento proksimaalisen hamstring-tendinopatian diagnostiikassa sekä hamstring-vammojen kirurgisen hoidon tulokset. Hamstring-vammamekanismeja ammattilaisjalkapalloilijoilla analysoineessa tutkimuksessa vammat syntyivät pääosin nopeissa liikkeissä, tyypillisesti sisältäen polven ojennuksen sekä lonkan ja vartalon koukistuksen, useimmin vaurioittaen biceps femoris -lihas-jännekompleksia. Sprintin ja venytyksen lisäksi myös sekatyyppisiä vammamekanismeja todettiin. Valtaosa (80 %) rectus femoris -vammoista miesammattilaisjalkapalloilijoilla tapahtui potkaisun aikana, ja ne aiheuttivat usein vähintään yhden jänteen täydellisen repeämän. Spurtin aikana syntyneet vammat johtivat myös täydellisiin repeämiin, kun taas suunnanmuutosten yhteydessä syntyi vain osittaisia repeämiä. Vakavia adductor longus -vammoja ammattilaisjalkapalloilijoilla analysoineessa tutkimuksessa todettiin, että nämä vammat aiheutuivat useimmiten suljetun kineettisen ketjun liikkeiden, esimerkiksi palloon kurottamisen, aikana. Tyypillisesti vammahetkellä havaittiin lonkan ojennus, loitonnus ja ulkokierto. Proksimaalisen hamstring-tendinopatian diagnostiikka voi olla erittäin haastavaa, ja vaivan hoitaminen voi olla vaikeaa. Tässä tutkimuksessa esitimme uuden kuvausasennon lonkka koukistettuna, ja osoitimme, että tästä asennosta on hyötyä kyseisen vamman magneettikuvausdiagnostiikassa. Systemaattisessa katsauksessa totesimme, että leikkaushoito johtaa hyviin tuloksiin hamstring-jännerepeämien hoidossa, etenkin akuuttien leikkausten yhteydessä.